Phytohaemagglutinin activation of T cells through the sheep red blood cell receptor. - O'Flynn, K; Krensky, A; Beverley, P; Burakoff, S; Linch, D (1985)
Expression of receptors for sheep red blood cells and the ability to proliferate in response to phytohaemagglutinin (PHA) are the traditional properties of human T cells, but the function of the sheep red cell receptor (the T11 antigen) is controversial and the mechanism of PHA-induced mitogenesis unclear. Mitogenesis involves a complex series of cell-mediated and factor-dependent interactions, but a rise in intracellular free calcium concentration, [Ca2+]i, seems to be an important primary event in T-cell activation. We have now investigated the effects of three monoclonal antibodies, previously shown to inhibit mitogen-induced proliferation, on T-cell [Ca2+]i. We find that anti-LFA-2 and OKT11, which react with the sheep red cell receptor, have no effect on [Ca2+]i, nor do they inhibit the rise in [Ca2+]i induced by concanavalin A (Con A) or the mitogenic anti-T3 monoclonal antibody UCHT1 (ref. 11). They do, however, block PHA-induced Ca2+ mobilization. Anti-LFA-1, which reacts with the lymphocyte function-associated antigen, has no effect on intracellular Ca2+. These studies suggest that the sheep red blood cell receptor is an activation pathway for T cells and that the effects of PHA are mediated through this pathway.